Comparison of pedicle screw fixation and hybrid instrumentation in adolescent idiopathic scoliosis - Çeçen, Gültekin Sıtkı; Gülabi, Deniz; Güçlü, Bülent; Çeçen Ayçiçek, Dilber; Oltulu, İsmail (Ekin Medical Publishing, 2016)
Objective: The purpose of this study was to compare pedicle screw fixation (PSF) with hybrid instrumentation (HI) in cases of adolescent idiopathic scoliosis (AIS). Methods: Thirty-eight patients with AIS who underwent PSF (n=19) or HI (n=19) between 2001 and 2011 were retrospectively reviewed. Patients had similar age at surgery and similar number of fused vertebrae. Operative time, intraoperative blood loss, and postoperative complications were compared between the 2 groups. Spinal radiographs for apical vertebral translation, global coronal balance, major curve Cobb angle, global sagittal balance, thoracic kyphosis, and lumbar lordosis were measured in all patients preoperatively and at 2-year follow-up; the results were then compared between the 2 groups. Postoperative correction was calculated for all patients and compared between the 2 groups. Results: The average time of surgery ofthe PSF group was significantly longer than that of the HI group (p<0.05). The amount of bleeding of the PSF group was significantly higher than the HI group (p<0.01). No statistically significant difference was found between the groups in respect to the development of complications (p>0.05). Both the major curve Cobb angle and the global sagittal balance showed greater improvement in the PSF group compared to the HI group (p<0.01). Postoperative correction was better in the PSF group than the HI group. Conclusion: The PSF system provided better improvement than the HI system in major curve Cobb angle and global sagittal balance, and postoperative correction was better in the PSF group than the HI group.
Keywords: Adolescent Idiopathic Scoliosis; Hybrid Instrumentation; Pedicle Screw Fixation